Involvement of the Reparative DNA Polymerase Pol X of African Swine Fever Virus in the Maintenance of Viral Genome Stability In Vivo - Redrejo-Rodríguez, Modesto (American Society for Microbiology, 2013)
The function of the African swine fever virus (ASFV) reparative DNA polymerase, Pol X, was investigated in the context of virus infection. Pol X is a late structural protein that localizes at cytoplasmic viral factories during DNA replication. Using an ASFV deletion mutant lacking the Pol X gene, we have shown that Pol X is not required for virus growth in Vero cells or swine macrophages under one-step growth conditions. However, at a low multiplicity of infection, when multiple rounds of replication occur, the growth of the mutant virus is impaired in swine macrophages but not in Vero cells, suggesting that Pol X is needed to repair the accumulated DNA damage. The replication of the mutant virus in Vero cells presents sensitivity to oxidative damage, and mutational analysis of viral DNA shows that deletion of Pol X results in an increase in the mutation frequency in macrophages. Therefore, our data reveal a biological role for ASFV Pol X in the context of the infected cell in the preservation of viral genetic information.